The role of GATA4 in mesenchymal stem cell senescence: A new frontier in regenerative medicine - M. Arockia Babu; Renuka Jyothi S; Irwanjot Kaur; Sachin Kumar; Naveen Sharma; M. Ravi Kumar; Pranchal Rajput; Haider Ali; Gaurav Gupta; Vetriselvan Subramaniyan; Ling Shing Wong; Vinoth Kumarasamy (Regenerative Therapy)
The Mesenchymal Stem Cell (MSC) is a multipotent progenitor cell with known differentiation potential towards various cell lineage, making it an appealing candidate for regenerative medicine. One major contributing factor to age-related MSC dysfunction is cellular senescence, which is the hallmark of relatively irreversible growth arrest and changes in functional properties. GATA4, a zinc-finger transcription factor, emerges as a critical regulator in MSC biology. Originally identified as a key regulator of heart development and specification, GATA4 has since been connected to several aspects of cellular processes, including stem cell proliferation and differentiation. Accumulating evidence suggests that the involvement of GATA4-nuclear signalizing in the process of MSC senescence-related traits may contribute to age-induced alterations in MSC behavior. GATA4 emerged as the central player in MSC senescence, interacting with several signaling pathways. Studies have shown that GATA4 expression is reduced with age in MSCs, which is associated with increased expression levels of senescence markers and impaired regenerative potential. At the mechanistic level, GATA4 regulates the expression of genes involved in cell cycle regulation, DNA repair, and oxidative stress response, thereby influencing the senescence phenotype in MSCs. The findings underscore the critical function of GATA4 in MSC homeostasis and suggest a promising new target to restore stem cell function during aging and disease. A better understanding of the molecular mechanisms that underlie GATA4 mediated modulation of MSC senescence would provide an opportunity to develop new therapies to revitalize old MSCs to increase their regenerative function for therapeutic purposes in regenerative medicine.